The Role of Informal Channels in Shaping Local Political Communication: Insights from Bogor, Indonesia - Toto Sugiarto; Roni Jayawinangun (Rescollacom (Research Collaborations Community), 2026)
The relationship between executive and legislative institutions is a key pillar of subnational governance in Indonesia, especially during the era of regional autonomy. This article examines how informal political mechanisms shaped political communication between the Mayor of Bogor and the Bogor City Council (DPRD) during the 2014–2019 period. The study employs a qualitative single-case design based on in-depth interviews with key political actors—including the mayor, council speaker, faction leaders, local media executives, and local political observers—complemented by document and media analysis. Data were analyzed using Miles, Huberman, and Saldaña's interactive model of data reduction, display, and conclusion drawing. The findings show that informal communication channels, such as interpersonal lobbying, private meetings, and social–religious gatherings, play a more decisive role than formal procedures in building trust, negotiating policy trade-offs, and preventing open conflict between the executive and legislature. Informal politics functions as a complementary and accommodating informal institution that fills the gaps in formal rules and enhances political resilience by providing an early warning and conflict prevention mechanism. Simultaneously, formal procedures remain essential as a framework for legitimacy and accountability. The article conceptualises these dynamics as a form of trust-based political communication within a hybrid political communication system at the local level and discusses their implications for democratic accountability and executive–legislative collaboration in Indonesia's semi-presidential context.